2016
DOI: 10.1097/ico.0000000000001107
|View full text |Cite
|
Sign up to set email alerts
|

Age-Stratified Analysis of Diabetes and Pseudophakia Effects on Corneal Endothelial Cell Density: A Retrospective Eye Bank Study

Abstract: Purpose To perform an age-stratified analysis of the effect of diabetes and pseudophakia on the corneal endothelial cell density. Methods A comparative analysis of donor characteristics from data supplied by the Lions Eye Institute for Transplant and Research on tissue harvested from July 1st, 2007 through May 23, 2014. The mixed-effects model was used to compare age-adjusted mean corneal endothelial cell density (ECD) between donors with and without diabetes. Results 20,026 non-diabetic donor eyes and 13,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…The mean ECD values in this study are lower than those obtained in other studies such as Schaub et al (phakic 2936 ± 262 cells/mm 2 , pseudophakic 2645 ± 200 cells/mm 2 ), but the donor population differs in terms of the lower proportion of pseudophakic eyes and the higher proportion of female donors compared with our study. Compared with other studies showing a negative influence of pseudophakia on corneal ECD [ 13 , 30 ], the negative influence determined in our study seems rather strong (378 cells/mm 2 less in pseudophakic eyes), although a direct comparison with other studies is not possible because of different study designs.…”
Section: Discussioncontrasting
confidence: 94%
“…The mean ECD values in this study are lower than those obtained in other studies such as Schaub et al (phakic 2936 ± 262 cells/mm 2 , pseudophakic 2645 ± 200 cells/mm 2 ), but the donor population differs in terms of the lower proportion of pseudophakic eyes and the higher proportion of female donors compared with our study. Compared with other studies showing a negative influence of pseudophakia on corneal ECD [ 13 , 30 ], the negative influence determined in our study seems rather strong (378 cells/mm 2 less in pseudophakic eyes), although a direct comparison with other studies is not possible because of different study designs.…”
Section: Discussioncontrasting
confidence: 94%
“…The variability in the shape and size of cells is of particular importance because it is associated with cell stress and has been associated with a higher likelihood of corneal decompensation after intraocular surgery. 9,10 The estimated effect of alcohol abuse on ECD was modest at 60.9 cells/mm 2 , a small percentage of the median ECD in this study. This suggests that the findings, although statistically significant, may not reach the threshold for clinical significance for most donors.…”
Section: Discussionmentioning
confidence: 57%
“…The variability in the shape and size of cells is of particular importance because it is associated with cell stress and has been associated with a higher likelihood of corneal decompensation after intraocular surgery. 9,10…”
Section: Discussionmentioning
confidence: 99%
“…Chocron et al [148] and Liaboe et al [145] reported lower levels of ECD in diabetes patients when compared to controls. Chen et al [147] described this endothelial loss only in patients between 21 and 60 years; subjects above this age did not have statistically significant differences when compared to healthy controls. Moreover, Kwon et al [143] report that age, previous cataract surgery, and diabetes were found to be the most important risk factors for deficient donor quality with respect to ECD.…”
Section: Diabetes and Endotheliummentioning
confidence: 96%